Fabrication and testing of short fiber composites made of used brush bristles as reinforcement combined with epoxy matrix. (2021) - Chandramohan, Naveen Kumar; Rajkumar, G.; Bhuvendran, Arun; John Alexis, S.
Abstract: The first thing a person touches when he wakes up in the morning is toothbrush and it has evolved a lot from chew sticks to cattle bone brush to the modern plastic toothbrush. For a few decades now we are using plastic toothbrush and once it is used or old it is thrown away and all these are dumped in landfills across the world. In a lifetime one human being approximately changes 300 toothbrushes, they are small and compact it is difficult to recycle them because they will be stuck in the machinery. This when thrown out will pollute the ocean, dry out oil resources and affects the habitat of sea mammals and other animals etc. In the US alone there are 1 Billion toothbrushes thrown away that will wrap the whole earth 4 times [1–3]. In this research the used toothbrush bristles made of nylon is used as a reinforcement combined with the epoxy matrix and a short fiber composite is fabricated using compression molding process. The composite is fabricated under three cases, case (i) Random orientation of the reinforcement, case (ii) 0 degree orientation of the reinforcement, case (iii) 45 degree orientation of the reinforcement. The fabricated composites are then tested for tensile and flexural strength. The fiber oriented at 45 degrees has better properties compared to other orientations.